PENGARUH CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE DAN DIVIDEND POLICY TERHADAP KINERJA PERBANKAN DI INDONESIA - Mutianingsih, Veronika; Usman, Bahtiar; Hartini, Hartini (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to examine the influence of corporate social responsibility, good corporate governance (institutional ownership and board size), and dividend policy on the financial performance of banking in Indonesia Stock Exchange (IDX) during the period of 2018 to 2022. A sample of 44 was selected using purposive sampling. The analysis was conducted using E-Views, and the results indicate that corporate social responsibility, good corporate governance, and dividend policy simultaneously affect financial performance. CSR and GCG (institutional ownership and board size) do not significantly influence banking performance in Indonesia, while dividend policy has a significant negative effect on banking performance. This study provides insights for banks and investors to consider dividend policy in managing their businesses and making investment decisions.